Study of Front Wheel Pressure on the Soil of Tractors with a Different Wheel Configuration - A. A. Akhmetov; Sh. A.U. Akhmedov (Сельскохозяйственные машины и технологии, 2019)
An increase in the power of the high-clearance tractor with the 3K2 wheel configuration (TTZ-811) and the weight of the machines coupled with it has led to an increase in the pressure of its running elements on the soil. The authors have proposed to replace it with a tractor with the 4K2 wheel configuration with an adjustable ground clearance (TTZ-1033), which has several advantages.Research purpose The study of the effect of the wheel configuration, travel speed and air pressure in the tire on the tractor's front wheel pressure on the soil.Materials and methods The authors have analytically determined the relationship between the contact area of a wheel tire with the soil on the tire parameters and the internal air pressure in it. To take measurements, load TAS607 sensors like with specially made nozzles have been used.Results and discussion It has been found that under similar conditions, the average pressure on the soil in the layer of 10-50 centimeters across the width of the front wheel tire of TTZ-811 is 19.0-27.6 kilopascals more as compared to TTZ-1033. It has been found that an increase in air pressure in the tire from 1.2 to 2.2 megapascals results in a n increase in average front wheel pressure on the soil in the seed layer (0-10 centimeters) of the TTZ-1033 tractor from 61.9 to 70.8 kilopascals, and of the TTZ-811 tractor – from 63.5 to 79.3 kilopascals. It has been revealed that at a depth of 10 centimeters, the pressure of the front wheel of the TTZ‑1033 tractor averaged 84.9-108.2 kilopascals, and at a depth of 50 centimeters – only 12.2-12.8 kilopascals. Under the same conditions, the average pressure` of the TTZ-811 tractor's front wheel decreases from 78.0-113.3 to 15.3-52.8 kilopascals.Conclusions The authors have stated that soil compaction with the front wheels of a tractor can be reduced by replacing a tractor with a 3K2 wheel configuration with a tractor with a 4K2 wheel configuration, as well as by increasing the tractor speed.